(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the role of gamification in developing students’ speaking skills in the English language learning context. With the growing need for interactive and student-centered teaching methods, gamification has emerged as an effective pedagogical tool. The study examines various gamified activities and their influence on learners’ oral fluency, accuracy, and motivation. Using qualitative and quantitative data collection methods, including classroom observations, interviews, and speaking assessments, the research demonstrates that gamification significantly enhances students’ speaking performance. Results indicate improved learner engagement, reduced speaking anxiety, and increased speaking time. The findings support integrating gamified methods into English language curricula to foster communicative competence.